Navigating (In)directness: The Translation of Javanese Directive Utterances into English in Film Subtitles - Emi Nursanti; Suhandano Suhandano; Sulistyowati Sulistyowati (Journal of Language and Literature, 2026)
Translating politeness and (in)directness in speech acts presents a considerable challenge in audiovisual translation, where cultural details are frequently lost.  This problem becomes much more apparent for languages with a complex politeness system, such as Javanese, when translated into English. This study investigates how the (in)directness and politeness of directive speech acts (DSAs) are translated from Javanese into English in film subtitles, focusing on the strategies employed and their pragmatic implications. A qualitative-dominant mixed-methods approach was applied to Javanese-English directive utterances from 20 short films produced by the Provincial Government of the Special Region of Yogyakarta. The results show that the direct translation (59.6%) was far from mere literal translation, as it involved significant modulation to preserve the source text’s illocutionary force, while translation shifts (40.4%) demonstrate the translator’s effort of pragmatic mediation. Specifically, 58.2% of the shifts toward enhanced directness were aimed at meeting subtitle constraints and improving clarity, while 41.8% of the shifts toward lessened directness were meant to conform to English norms of negative politeness, which occasionally compromise speaker intent. These findings affirm that politeness in translation is a dynamic variable that needs adjusting. In dealing with such an issue, translators act as intercultural mediators who should navigate the spectrum between directness and indirectness in two different cultures.